A Copper‐based Supramolecular Nanocapsule that Enables Straightforward Purification of Sc3N‐based Endohedral Metallofullerene Soots. Issue 15 (20th February 2017) - Fuertes‐Espinosa, Carles; García‐Simón, Cristina; Castro, Edison; Costas, Miquel; Echegoyen, Luis; Ribas, Xavi
Abstract: A self‐assembled Cu II ‐based nanocapsule enables efficient and straightforward isolation of Sc3 N@C80 from arc‐processed raw soot. The newly designed Cu II ‐based supramolecular nanocapsule 5⋅ (OTf)8 was used to effectively entrap fullerenes and endohedral metallofullerenes (EMFs) with different affinities depending on their size and shape. Moreover, we took advantage of the sharply different entrapment abilities of the 5⋅ (OTf)8 cage in the solid state versus in solution to encapsulate all the species with the exception of Sc3 N@C80 (both I h and D 5h isomers), which remains pure in solution. HPLC quantification determined that up to 85 % of the total Sc3 N@C80 content in the initial mixture was recovered in very high purity (>99.5 %). The complete release of the encapsulated species with an orthogonal solvent‐washing strategy regenerates 5⋅ (OTf)8 ready to be re‐used. This approach opens new opportunities for EMFs purification. Abstract : A fullerene clean : Purification of Sc3 N@C80 contained in Sc3 N‐based fullerene soots is achieved by using a Cu II ‐based supramolecular nanocapsule, reaching >99.5 % purity and up to 85 % recovery of the Sc3 N@C80 present in the initial mixture (see figure).